A 1.7 dBm OP1dB D-Band Up-Conversion Mixer Utilizing Adaptive Back-Gate Bias in 22 nm FDSOI - Huang, Tianzhu; Hetterle, Philip; Engelmann, Andre; Probst, Florian; Schrotz, Albert-Marcel; Weigel, Robert; Fischer, Georg (2024 Asia-Pacific Microwave Conference, 2024)

A 21 GHz Bandwidth 30 dB Gain VGA for 6G Basband Systems in 22 nm FDSOI - Hetterle, Philip; Engelmann, Andre; Scheller, Kai; Huang, Tianzhu; Weigel, Robert; Franchi, Norman (German Microwave Conference (GEMIC), 2025)
This paper presents a 5-stage wideband variable gain amplifier (VGA) integrated in 22 nm fully-depleted silicon-on-insulator (FDSOI) CMOS technology. The circuit comprises three different core circuit topologies, composed by an input buffer, three gain control stages and a high-power ouput stage. The VGA achieves 30 dB gain with a power consumption of 44 mW, exhibiting a continuous tuning range of 33 dB, covering a 3 dB bandwidth of 21 GHz, while occupying a area of 0.077 mm2. The VGA is optimized for operation within high-data rate 6G receiver system
Keywords: CMOS; FDSOI; VGA; baseband; low voltage; mobile communication; IC; 6G.

A 3-Stacked 10.2 dBm OP1dB D-Band Power Amplifier in 22 nm FDSOI for 6G Communication - Huang, Tianzhu; Engelmann, Andre; Hetterle, Philip; Probst, Florian; Weigel, Robert (2023 Asia-Pacific Microwave Conference, 2023)
This paper proposes a high-linearity 3-stacked D-band power amplifier (PA) for 6G communication. The PA is fabricated in 22 nm fully-depleted silicon-on-insulator (FDSOI) CMOS technology and consists of four stages, including three driver stages. The capacitive neutralization approach is adopted in all stages for gain-boosting. Transistor stacking is applied in the output stage for high output power and linearity. The circuit achieves a peak power gain of 23.8 dB at 135 GHz with a 3-dB bandwidth of 16 GHz. A maximum measured output power of 13 dBm, an output referred 1-dB compression point OP1dB of 10.2 dBm, and a peak power-added efficiency (PAE) of 9.9% are attained, while occupying only 0.081 mm² of chip are
Keywords: CMOS; D-band; FDSOI; high linearity; mm-wave; power amplifier (PA); stacked amplifier; 6G

Advanced PA Concepts and Technology for 5G/6G Power Amplifier Applications - Loose, Michael; Deublein, Alexander; Engelmann, Andre; Illmer, Andreas; Huang, Tianzhu; Riess, David; Weigel, Robert; Fischer, Georg (Berlin 6G Conference 2024, 2024)

A Low Voltage Folded Gilbert Cell Mixer for 6G Communication Systems - Hetterle, Philip; Engelmann, Andre; Probst, Florian; Huang, Tianzhu; Weigel, Robert (Asia-Pacific Microwave Conference (APMC), 2023)
This paper presents the design of a folded Gilbert cell D-band down-conversion mixer manufactured in a 22 nm fully-depleted silicon-on-insulator (FDSOI) CMOS technology. The mixer runs on a supply voltage of 800 mV and consumes a power of 28 mW. The device achieves a conversion gain of -7 dB while maintaining a broad bandwidth of 30 GH
Keywords: CMOS; D-band; FDSOI; Gilbert cell; down-conversion; low voltage; mixer; mm-wave; mobile communication; 6G